Current Status of Cognitive Remediation for Psychiatric Disorders: A Review - Kim, Eun Jin; Bahk, Yong-Chun; Oh, Hyeonju; Lee, Won-Hye; Lee, Jong-Sun; Choi, Kee-Hong (Frontiers in Psychiatry, 2018)
Cognition is an important factor that affects daily functioning and quality of life. Impairment in cognitive function is a common symptom present in various psychological disorders, which hinders patients from functioning normally. Given that cognitive impairment has devastating effects, enhancing this in patients should lead to improvements in compromised quality of life and functioning, including vocational functioning. Over the past 50 years, several attempts have been made to improve impaired cognition, and empirical evidence for cognitive remediation (CR) has accumulated that supports its efficacy for treating schizophrenia. More recently, CR has been successfully applied in the treatment of depressive disorders, bipolar disorders, attention deficit/hyperactivity disorder, and anorexia nervosa. This study critically reviews recent CR studies and suggests their future direction. This study aimed to provide a modern definition of CR, and examine the current status of empirical evidence and representative CR programs that are widely used around the world.